Pengaruh Durasi Steam terhadap Kualitas Arang Aktif Limbah Sagu (The Effect of Steam Duration on Quality and Characteristics of Activated Charcoal of Sago Waste) - Siruru, Herman; Syafii, Wasrin; Wistara, Nyoman J; Pari, Gustan (Jurnal Ilmu dan Teknologi Kayu Tropis, 2018)
Sago waste is a potential biomass that can be used as active charcoal raw material. The objectives of this research were to know the effect of steam duration on quality and characteristics of activated charcoal of sago waste. Carbonization process was carried out at 400 ⁰C for four hours, then activation was carried out at 100 ml bar steam pressure, at a temperature of 800 ⁰C with variations of steam duration 60, 80 and 100 minutes and activation without steam, only heating for 60 minutes. The proximate test used the SNI standard, observed the functional group using Fourier Transform Infrared Spectrophotometer (FTIR) and observed the active charcoal structure using X-ray diffraction (XRD). The results showed that the yield, moisture content, volatile, ash content, fixed carbon, iodine absorption of activated charcoal of sago bark and sago soft core were, respectively, 39.22–84.10%, 4.63–6.39%, 3.03–5.06%, 7.74–33.43%, 61.54–88.63%, 158.60–972.60 mg g-1. XRD analyzes showed that the degree of crystalline activated charcoal of sago bark waste with the highest steam time of 100 minutes (35.98%) compared with the degree of crystalline other activated charcoal is only about 20.57-7.30%. FTIR spectroscopy results from activated charcoal of sago waste also identified nitrogen compounds such as NO2 at wave numbers 1370-1390 cm-1; 1530-1560 cm-1; 1620-1660 cm-1 and phosphorus compounds such as P-S at 200-500 cm-1 wave number; P=S at the wave number 500-850 cm-1.Keywords: carbonization, active charcoal, sago, steam